Segmented assimilation, neighborhood disadvantage, and Hispanic immigrant health. (January 2016) - Akresh, Ilana Redstone; Do, D. Phuong; Frank, Reanne
Abstract: We use a subset of Hispanics from the New Immigrant Survey, a nationally representative data set on immigrants recently granted legal permanent residency (n = 2245), to examine whether the relationship between assimilation and health is modified by neighborhood disadvantage and, in doing so, carry out an empirical test of the segmented assimilation hypothesis. Results indicate that assimilation in the least disadvantaged neighborhoods can be protective against poor health. Specifically, more assimilated men and women in the lowest disadvantage neighborhoods have a lower likelihood of self-reported poorer health and being overweight, respectively; no link was found in higher disadvantage neighborhoods. Assimilation was not found to be associated with self-reported health for women or BMI for men, regardless of neighborhood disadvantage level. Overall, we find some evidence supporting the hypothesis that the effects of assimilation on health depend on the context in which immigrants experience it. Highlights: We study whether contextual disadvantage shapes the link between assimilation and health. Assimilation can protect against poor health in low disadvantage areas. Assimilation in more disadvantaged neighborhoods loses its protective effect.